Generation Z Leadership In The Digital Era: A Qualitative Analysis Of Technology Proficiency and Emerging Leadership Pattern - Damiasih (International Journal of Management and Business Economics, 2026)
The current demographic bonus is dominated by the presence of Generation Z, defined as those born between 1995 and 2012. This generation has grown up in a digital environment characterized by rapid technological and informational advancements, resulting in distinct leadership characteristics and perspectives. This study aims to analyze the leadership potential of Generation Z, identify their key characteristics as leaders in the digital era, and examine the role of technological competence in supporting future leadership. This research employs a qualitative descriptive approach, utilizing primary data obtained through interviews with four informants who lead their respective work units, as well as secondary data derived from relevant literature reviews. The findings indicate that Generation Z possesses strong leadership potential, with a tendency toward collaborative, supportive, and democratic leadership styles. Moreover, Generation Z demonstrates high adaptability, strong technological skills that facilitate communication and task completion, and a people-oriented approach that emphasizes togetherness in workplace interactions. These findings contribute to a deeper understanding of emerging generational leadership patterns and their implications for organizational development in the digital era.